Safety requirements for electrical equipment for measurement, control and laboratory use. Particular requirements for autoclaves and sterilizers using toxic gas for the treatment of medical materials, and for laboratory processes Part 2-042, (15th July 1997) - British Standards Institution,
No abstract available